Either Extremist, Nationalist, or Based on SARA: Meanings of Radicalism in Twitter in Indonesia, 2019-2021 - Mohammad Nuruzzaman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Media technologies is not only significant for human life, but also contributes to impact where the space is also used to spread radicalism discourse in the form of hate speech in a wide range. Reflecting on McLuhan's theory, communication phenomenon in the use of media, apart from paying attention to the context of the message content on a particular platform, it must also show the capabilities and it’s features. In understanding the context of the message on a particular platform, my study on twitter in Indonesia shows how Twitter has expanded from a source of real-time information into facilitating radicalism and accelerating opportunities for radicalization. However, different from the popular assumption that radicalism has only single-meaning, my paper wants to describe that the meaning of radicalism in Indonesia is so diverse based on how the media and messages can only significantly shape the way of communication if it is supported by ideological aspects and features of the technology itself.